High Affinity Humanized Antibodies without Making Hybridomas; Immunization Paired with Mammalian Cell Display and In Vitro Somatic Hypermutation - McConnell, Audrey D.; Do, Minjee; Neben, Tamlyn Y.; Spasojevic, Vladimir; MacLaren, Josh; Chen, Andy P.; Altobell, III, Laurence; Macomber, John L.; Berkebile, Ashley D.; Horlick, Robert A.; Bowers, Peter M.; King, David J. (PLOS ONE, 2012)
A method has been developed for the rapid generation of high-affinity humanized antibodies from immunized animals without the need to make conventional hybridomas. Rearranged IgH D(J) regions were amplified from the spleen and lymph tissue of mice immunized with the human complement protein C5, fused with a limited repertoire of human germline heavy chain V-genes to form intact humanized heavy chains, and paired with a human light chain library. Completed heavy and light chains were assembled for mammalian cell surface display and transfected into HEK 293 cells co-expressing activation-induced cytidine deaminase (AID). Numerous clones were isolated by fluorescence-activated cell sorting, and affinity maturation, initiated by AID, resulted in the rapid evolution of high affinity, functional antibodies. This approach enables the efficient sampling of an immune repertoire and the direct selection and maturation of high-affinity, humanized IgGs.